Encore Café: An Innovative and Effective Congregate Nutrition Program. Issue 4 (2nd October 2021) - Schultz, Savannah; Francis, Sarah L.; Russell, Carlene; Getty, Tim; Bauman, Alexandra; Shelley, Mack
Abstract: Effective community food and nutrition programs are imperative for supporting older adults health and well-being. This three-part study examined to what extent the innovative congregate nutrition program (CNP), Encore Café, and targeted marketing campaign influenced CNP utilization, CNP program satisfaction, and overall CNP impact (e.g., nutritional risk, dietary practices, and loneliness). The Encore Café resulted in increases of 386% in meal distribution and 3, 164% in CNP participants during a two-year period compared to a 20.8% reduction at traditional meal sites across the state. Total CNP satisfaction (food and dining) was high for both the Encore Café and Traditional CNP. Encore Café participants maintained their nutritional status and experienced significant reductions in emotional loneliness ( p  = 0.017) and dietary intake frequencies of processed meat ( p  = 0.027) compared to non-CNP participants. Utilizing a client-centered approach in marketing and programming for the Encore Café shows promising results for improving the utilization and effectiveness of the CNP.